2014
DOI: 10.1177/0333102414564893
|View full text |Cite
|
Sign up to set email alerts
|

A multidirectional epicrania fugax

Abstract: A multidirectional epicrania fugaxDear Editor, Epicrania fugax (EF) has been recently classified as a primary headache in the Appendix of the International Classification of Headache Disorders, 3rd edition, beta version (1). EF is characterized by a brief paroxysmal pain following a lineal or zigzag trajectory across the head surface. EF pain typically moves between two distant points through the territories of different nerves. In all the reported cases the pain was strictly unilateral with either forward or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
1
18
0
1
Order By: Relevance
“…EF, a recently described novel headache syndrome, characterized by brief pain paroxysms starting in a particular area of the posterior scalp, and rapidly radiating forwards along a linear trajectory to reach the ipsilateral forehead, eye, or nose in a few seconds (Pareja et al 2008 , 2012a ; Guerrero et al 2010 ; Porta-Etessam et al 2010 ; Mulero et al, 2011 ; Cuadrado et al 2013 ; Jin and Wang 2013 ), has now been incorporated in the appendix of the third edition of the International Classification of Headache Disorders (ICHD-III beta) (IHS 2013 ; Belvis et al 2015 ). A typical pain trajectory of EF is different from that of the currently reported coronal line-shaped head pain, whereas, recent reports have shown that the pain trajectory of EF may distribute in different area (de la Cruz et al 2015 ), even in multiple directions (Cuadrado et al 2015 ). Furthermore, Pareja and Bandres reported an interictal persistent line-shaped head pain in EF (Pareja and Bandres 2015 ).…”
Section: Discussion and Evaluationmentioning
confidence: 58%
“…EF, a recently described novel headache syndrome, characterized by brief pain paroxysms starting in a particular area of the posterior scalp, and rapidly radiating forwards along a linear trajectory to reach the ipsilateral forehead, eye, or nose in a few seconds (Pareja et al 2008 , 2012a ; Guerrero et al 2010 ; Porta-Etessam et al 2010 ; Mulero et al, 2011 ; Cuadrado et al 2013 ; Jin and Wang 2013 ), has now been incorporated in the appendix of the third edition of the International Classification of Headache Disorders (ICHD-III beta) (IHS 2013 ; Belvis et al 2015 ). A typical pain trajectory of EF is different from that of the currently reported coronal line-shaped head pain, whereas, recent reports have shown that the pain trajectory of EF may distribute in different area (de la Cruz et al 2015 ), even in multiple directions (Cuadrado et al 2015 ). Furthermore, Pareja and Bandres reported an interictal persistent line-shaped head pain in EF (Pareja and Bandres 2015 ).…”
Section: Discussion and Evaluationmentioning
confidence: 58%
“…10 To end with the proposed variants of EF, one striking case presented zigzag pain paroxysms in multiple directions: some of them followed a classical backward radiation on either side of the scalp, some followed a diagonal trajectory from one occipital area to the opposite frontal region, and finally some crossed the head from one temple to the other in a coronal radiation akin to the paroxysms described in our series. 11 We report 4 patients suffering lancinating and stereotyped pain paroxysms with a transverse radiation. Apart from this trajectory, the similarities to all cases with EF described up to now are evident, when considering pain characteristics (duration, intensity, character or motion of the pain following a lineal or zigzag trajectory), or the existence of a fixed stemming area, which can remain painful in between attacks.…”
Section: Discussionmentioning
confidence: 98%
“…A facial variant of EF has also been proposed after a description of 5 patients with a paroxysmal pain starting in the lower face and radiating upwards with linear trajectory . To end with the proposed variants of EF, one striking case presented zigzag pain paroxysms in multiple directions: some of them followed a classical backward radiation on either side of the scalp, some followed a diagonal trajectory from one occipital area to the opposite frontal region, and finally some crossed the head from one temple to the other in a coronal radiation akin to the paroxysms described in our series …”
Section: Discussionmentioning
confidence: 99%
“…The phenotype of EF has become even broader during the last few years. For instance, it has been reported that pain paroxysms may occur at shifting sides,1,7 along the mid-sagittal plane,9 with coronal radiation10 or even in a multidirectional fashion 11. A facial variant of EF4 has also been proposed.…”
Section: Introductionmentioning
confidence: 99%